ISOLATION AND IDENTIFICATION OF HYDATID CYST FLUID-ASSOCIATED BACTERIA ISOLATED FROM CATTLE AND SHEEP LUNGS IN SOUTHERN PARTS OF LRAQ (British Journal of Global Ecology and Sustainable Development, 2023)
Echinococcus granulosus is a dominant disease, infection occurring during the larval stage and affecting hosts, including cattle as the intermediate host and dogs in particular as the definitive host, who become infected with hydatid cysts. Therefore, the study included the diagnosis of bacteria associated with hydatid fluids isolated from intermediate hosts, including the lungs of cows and sheep. Between February and April 2022, 75 lung samples were taken from sheep and cows infected with hydatid cysts. A set of phenotypic, diagnostic and microscopic tests was conducted, and to confirm that, the Vitek test was performed. The infection rates of bacteria isolated from sheep lungs were higher than those isolated from cow lungs, as it reached 98% in sheep compared to 88% in cows. The results of biochemical tests for Escherichia. coli, Shigella spp. Proteus spp. Providencia spp, In addition, 7 isolates were diagnosed using Vitek technology, 3 isolates belonged to cattle lungs, two isolates were identified as Serratia ficaria and one isolate was identified as Aeromonas hydro/cavia. The remaining five isolates belong to sheep lungs. Two of them belong to Alcaligenes spp, and three isolates belong to Proteus hauseri, Planococcus massiliensis, and Moellerella wiscousensis, where the results were not identical to the results of the biochemical diagnosis. Therefore, we conclude from the current study that there are types of bacteria associated the hydatid cyst that differ according to the affected organ.